Ursolic and Oleanolic acid effects on cellular cholesterol and impact on signaling pathways of cell death and proliferation - Machado, Cátia Daniela Oliveira Lima Ferreira (2015)
Dissertação de mestrado em Bioquímica Aplicada (área de especialização em Biomedicina)